Associations Between Hemoglobin, Insomnia, Nausea, Cancer-Related Fatigue in Chemotherapy Outpatients: Implications for Clinical Nursing Management - Hendra Dwi Cahyono; zahra saad; Ina Martiana; Anita Fatarona; Fitri Kusumasa (Universitas Tribhuwana Tunggadewi, 2026)
Cancer-related fatigue (CRF) is one of the most prevalent and distressing symptoms experienced by patients with cancer during chemotherapy. CRF is multidimensional in nature and is often associated with biological factors and co-occurring symptoms such as anemia, insomnia, and nausea and vomiting. Objective: This study aimed to examine the associations between hemoglobin levels, insomnia, nausea and vomiting, and cancer-related fatigue among patients undergoing outpatient chemotherapy. A quantitative observational study with a cross-sectional design was conducted. A total of 111 patients receiving outpatient chemotherapy were recruited using consecutive sampling. Cancer-related fatigue was assessed using the Fatigue Assessment Scale (FAS), insomnia was measured using the Insomnia Severity Index (ISI), and nausea and vomiting were assessed using the Rhodes Index of Nausea, Vomiting, and Retching (RINVR). Hemoglobin levels were obtained from patients’ medical records. Data were analyzed descriptively and using bivariate Spearman’s correlation analysis. The mean hemoglobin level was 11.43 ± 2.05 g/dL. The mean scores for cancer-related fatigue, insomnia, and nausea and vomiting were 30.12 ± 9.06, 16.77 ± 5.28, and 7.92 ± 7.45, respectively. Spearman’s correlation analysis revealed a significant negative association between hemoglobin levels and cancer-related fatigue (r = ?0.293; p = 0.002). In contrast, insomnia (r = 0.277; p = 0.003) and nausea and vomiting (r = 0.278; p = 0.003) were positively and significantly associated with cancer-related fatigue. Cancer-related fatigue among chemotherapy outpatients is significantly associated with hemoglobin levels, insomnia, and nausea and vomiting. Routine monitoring of hemoglobin levels, along with systematic screening for sleep disturbances and nausea, is recommended to support more effective nursing interventions for managing cancer-related fatigue in outpatient chemotherapy settings.